Credit information in emerging markets: the rating agencies and credit risk reports, Peruvian experience - Cisneros, Diego (2012)
This paper seeks to develop a literature review within the main aspects of credit information in emerging markets, important aspect considering that several companies, including the small enterprises, are looking forward to “go” to capital markets. Thus, we will analyze the role of rating agencies and credit bureaus (credit risk report) in the Peruvian market, considering the current state of economic growth that comes through and, the potential of capital market that comes with MILA (Integrated Latin American Market). Besides, this information will become relevant in the following months, because the actual financial crisis in several countries all over the world (focus in Europe, but it could move to some BRICS – Brazil, Russia, India, China and South Africa – or Latam Countries) has generated a new map in “rating scores” (Note 1) so the questions that we tried to answer is if this unique change is relevant? Or it should be complemented in order to have a significant impact in the market and for the investors.